Rancang Bangun Website Promosi PT. Sejahtera Dunia Akhirat (Studi Kasus : Kantor Cabang Limawaktu) - Umami, Nurul; Hidayat, Alfin; Panduardi, Farizqi (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
This study aims to develop a promotional website for PT. Sejahtera Dunia Akhirat's Limawaktu branch, an electronics store. The background of this research is the Limawaktu branch's need to transform their static website into a dynamic one to enhance user experience and the effectiveness of their online product promotions. The RAD (Rapid Application Development) method was chosen for this project due to its suitability for fast and iterative product development. The promotional website developed includes features for both customers and the admin side. After the website was developed, functionality testing was conducted using the User Acceptance Testing (UAT) method. The development results showed that out of 43 test cases, 41 were successful (95.35%) and 2 failed (4.65%). The system's success in meeting user needs reached 95.35%, indicating that the developed promotional website effectively improves the marketing and stock control for the Limawaktu store. The conclusion of this study is that the use of the RAD method in developing promotional websites is proven effective in producing systems that meet specific user needs.